The kinase domain of CK1δ can be phosphorylated by Chk1 - Böhm, Thomas; Meng, Zhigang; Haas, Philipp; Henne-Bruns, Doris; Rachidi, Najma; Knippschild, Uwe; Bischof, Joachim (Bioscience Biotechnology and Biochemistry, 2019)
Members of the casein kinase 1 (CK1) family are key regulators in numerous cellular signal transduction pathways and in order to prevent the development of certain diseases, CK1 kinase activity needs to be tightly regulated. Modulation of kinase activity by site-specific phosphorylation within the C-terminal regulatory domain of CK1δ has already been shown for several cellular kinases. By using biochemical methods, we now identified residues T161, T174, T176, and S181 within the kinase domain of CK1δ as target sites for checkpoint kinase 1 (Chk1). At least residues T176 and S181 show full conservation among CK1δ orthologues from different eukaryotic species. Enzyme kinetic analysis furthermore led to the hypothesis that site-specific phosphorylation within the kinase domain finally contributes to fine-tuning of CK1δ kinase activity. These data provide a basis for the extension of our knowledge about the role of site-specific phosphorylation for regulation of CK1δ and associated signal transduction pathways.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Casein kinase 1; Checkpoint kinase 1; Enzyme kinetics; Phosphopeptide analysis; Site-specific phosphorylation